The anthropology of anger civil society and democracy in Africa - Monga, Célestin (Lynne Rienner Publishers, 1996)
Many scholars have argued that the ongoing democratization process in Africa is doomed to fail because the political reforms have been essentially imposed by external donors. Others have challenged the very roots of the current changes, alleging that Africa needs cultural and economic adjustments before being ready for sustainable democracy. Celestin Monga argues that both views are wrong. African peoples, he demonstrates, have been trying for decades to challenge authoritarianism, but their patterns of behaviour could not be captured by the classical tools used for measuring political participation and political culture. "The Anthropology of Anger" sheds light on the continent's long tradition of an indigenous form of activism. Analyzing social changes from a grassroots perspective, Monga shows that the quest for freedom in Africa is deeply entrenched. He goes beyond discussion of anger, ethnic conflicts and despair to provide new frameworks for understanding Africa's internal social dynamics, and to reveal how Africa - an unusual political "market" with highly creative political entrepreneurs - is renewing democratic theory.